Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Guru di SMK Sariwangi Tasikmalaya - Abdul Hakim (Jurnal Visi Manajemen, 2025)
This research is motivated by the phenomenon of declining teacher performance at SMK Sariwangi Tasikmalaya, which is suspected to be caused by low work motivation and a lack of work discipline. This issue is crucial because teacher performance is one of the key factors in achieving educational goals. Therefore, the purpose of this study is to empirically examine the influence of work motivation and work discipline on teacher performance. This study employed a quantitative approach with a survey method. The population consisted of all 38 teachers at SMK Sariwangi Tasikmalaya, and the sampling technique used was saturated sampling. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was carried out using multiple linear regression to determine both the partial and simultaneous effects of the independent variables on the dependent variable. The results showed that work motivation has a positive and significant effect on teacher performance, and work discipline also has a positive and significant effect on teacher performance. These findings emphasize that improving motivation through rewards, support, and a conducive work environment, as well as strengthening discipline through compliance with school rules and teaching responsibilities, are important factors in optimizing teacher performance. The implication of this research highlights the need for managerial strategies in human resource management, particularly in education, to enhance learning quality and achieve educational objectives.